A Comprehensive Study On Environmental Ethics In Classical Sanskrit Literature (Journal of Namibian Studies : History Politics Culture, 2023)
Sanskrit literature is abundant not only in its grammatical structure and romantic expression, but also in its insights into the environment, its degradation, and the imperative to save it. These themes arise frequently in many circumstances anytime the study of this literature is undertaken. This study investigates the importance of the environment in Sanskrit Literature. Throughout the course of human evolution on Earth, there has been a simultaneous existence of human life and the environment. The environment has provided mankind with unpolluted air, uncontaminated water, and surroundings free from toxins. Throughout history, every religion worldwide has consistently prioritized the environment. It is necessary for individuals living in society to comprehend the significance of maintaining the purity of these components. He should be aware of the advantages of consuming fresh water, air, and food. In order to maintain excellent health, it is crucial for individuals to consume nutritious food, consume clean water, and reside in an environment free from pollution.